The relationship of single-strand breaks in DNA to breast cancer risk and to tissue concentrations of oestrogens. (3rd October 2017) - Sahadevan, Mathavi; Lee, Oukseub; Muzzio, Miguel; Phan, Belinda; Jacobs, Lisa; Khouri, Nagi; Wang, Jun; Hu, Hong; Stearns, Vered; Chatterton, Robert T.
Abstract: Context: Clinical study of breast cancer patients in Chicago, IL, USA. Objective: Ascertain the utility of measurements of single-strand breaks (SSB) in DNA for assessment of breast cancer risk. Methods: Fine-needle aspirates of the breast, SSB by nick translation, percent breast density (PBD), Gail model risk, cumulative methylation index (CMI), enzymes of DNA repair and tissue antioxidants. Results: DNA repair enzymes and 4-hydroxyestradiol were negatively associated with SSB; CMI and PBD were positively associated. Conclusions: Quantitative measurement of SSBs by this procedure indicates the relative number of SSBs and is related to promoter methylation, antioxidant availability and percent breast density.